Addressing Financial and Regulatory Challenges in Logistics Hub Development - Cupiadi, Hedi; Siswanti, Tutik (Yayasan Sinergi Kawula Muda, 2025)
Logistics hubs are integral to regional economic development, offering significant contributions to growth through improved connectivity, trade facilitation, and job creation. This study aims to explore the economic, infrastructural, and governance-related aspects of logistics hubs, synthesizing empirical findings from a wide range of global case studies. Using a systematic review methodology, the study examines the role of multimodal infrastructure, digital technologies, and public-private partnerships in optimizing the performance of logistics hubs. Key findings show that while logistics hubs stimulate economic growth and enhance regional competitiveness, systemic barriers such as regulatory inefficiencies and financial constraints limit their full potential. Additionally, the integration of sustainable practices and social governance is critical for ensuring long-term success. The study highlights the importance of a holistic, cross-sectoral approach to logistics hub development and offers policy recommendations for overcoming existing challenges. Future research should focus on underrepresented regions and adopt interdisciplinary methodologies to address the complex dynamics of logistics hubs in diverse contexts.